PENGARUH PEMBERIAN MATA KULIAH PENGEMBANGAN KEWIRAUSAHAAN TERHADAP MINAT DAN KETERAMPILAN BERWIRAUSAHA MAHASISWA PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Junaidi Sagir; L. Hamdani Husnan; Mulyadi Mulyadi (Master of Management, Mataram University, 2020)
The objectives of this study were to know the effect of entrepreneurship education toward entrepreneurial interest and skills in the Faculty of Economics and Business, Universit y of Mataram. This study was causal research in which there were 100 students as respondents. Data were obtained by using a questionnaire and analyzed by simple linear regression through Partial Least Square (PLS). The results showed that: entrepreneurship education had a positive and significant effect on Entrepreneurial Interest. Entrepreneurship Education had a positive and significant effect on Entrepreneurial Skills. Entrepreneurial Interest had positivity and significance on Entrepreneurial Skills,